Photoinduced Cross‐Linking of Dynamic Poly(disulfide) Films via Thiol Oxidative Coupling. Issue 2 (26th October 2015) - Feillée, Noémi; Chemtob, Abraham; Ley, Christian; Croutxé‐Barghorn, Céline; Allonas, Xavier; Ponche, Arnaud; Le Nouen, Didier; Majjad, Hicham; Jacomine, Léandro
Abstract : Initially developed as an elastomer with an excellent record of barrier and chemical resistance properties, poly(disulfide) has experienced a revival linked to the dynamic nature of the S–S covalent bond. A novel photobase‐catalyzed oxidative polymerization of multifunctional thiols to poly(disulfide) network is reported. Based solely on air oxidation, the single‐step process is triggered by the photodecarboxylation of a xanthone acetic acid liberating a strong bicyclic guanidine base. Starting with a 1 μm thick film based on trithiol poly(ethylene oxide) oligomer, the UV‐mediated oxidation of thiols to disulfides occurs in a matter of minutes both selectively, i.e., without overoxidation, and quantitatively as assessed by a range of spectroscopic techniques. Thiolate formation and film thickness determine the reaction rates and yield. Spatial control of the photopolymerization serves to generate robust micropatterns, while the reductive cleavage of S–S bridges allows the recycling of 40% of the initial thiol groups. Abstract : The first oxidative photopolymerization of polythiol film to poly(disulfide) network is described. The process is simple, efficient (100% conversion in a matter of minutes), highly selective (no overoxidation), and occurs under ambient conditions. The essential chemistry relies on photogenerated superbases promoting the formation of thiolate anions, which are then subjected to air oxidation.